Thyroid tumor ratio: Improving the assessment of the impact of size in pediatric thyroid cancer. Issue 6 (23rd March 2022) - Paik, Connie; Osterbauer, Beth; Sahyouni, Grace; Park, Soyun; Gomez, Gabriel; Kwon, Daniel; Austin, Juliana
Abstract: Background: The impact of thyroid nodule size is less useful in children who have smaller thyroid volumes than in adults. We investigate using a novel thyroid tumor ratio measurement in children with thyroid cancer. Methods: Patient and pathologic characteristics were investigated via Student's t ‐test in a univariate analysis for any correlation with the log‐transformed tumor ratio, followed by a multivariate linear regression. Results: Of 75 patients with malignancy and tumor ratio information, mean ratio decreased with increasing age ( p = 0.04). Out of several clinical factors, patients with lymph node metastases and those treated with postoperative radioactive iodine had significantly higher mean tumor ratios on multivariate analysis ( p = 0.04 for both factors). Conclusions: Our study is the first to describe thyroid tumor volume in pediatric thyroid cancer and shows that increased tumor ratio was associated with indicators of more advanced disease such as lymph node metastases and use of radioactive iodine.